1997
DOI: 10.1073/pnas.94.17.9504
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an amino acid-selective channel protein present in the chloroplastic outer envelope membrane

Abstract: The reconstituted pea chloroplastic outer envelope protein of 16 kDa (OEP16) forms a slightly cationselective, high-conductance channel with a conductance of ⌳ ‫؍‬ 1,2 nS (in 1 M KCl). The open probability of OEP16 channel is highest at 0 mV (P open ‫؍‬ 0.8), decreasing exponentially with higher potentials. Transport studies using reconstituted recombinant OEP16 protein show that the OEP16 channel is selective for amino acids but excludes triosephosphates or uncharged sugars. Crosslinking indicates that OEP16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
152
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(160 citation statements)
references
References 52 publications
8
152
0
Order By: Relevance
“…Aligning this sequence with protein sequences found in the databases revealed that it matched a region of the previously identified outer plastid envelope membrane protein Oep16 of pea (39) and barley (40) (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aligning this sequence with protein sequences found in the databases revealed that it matched a region of the previously identified outer plastid envelope membrane protein Oep16 of pea (39) and barley (40) (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Almost certainly, the 16-kDa protein is identical with Oep16. This protein had been proposed to form an amino acid-selective channel protein in the outer envelope of pea chloroplasts (39). The crosslinking (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the seed-specific overexpression of a plasma membrane-localized amino acid permease in pea led to increased amino acid supply and OEP16 transcripts in embryos. Together with the in vitro selectivity of Ps-OEP16 for amino acids (36), it thus seems very likely that OEP16 is involved in amino acid transport across the outer envelope membrane of plastids. AroGP1 is a polygalacturonase converter, which is secreted to the apoplast and plays a role in regulating pectin metabolism during fruit ripening of tomato (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…According to phenotype analysis of an OEP16.1 knockout line in Arabidopsis it was then postulated that OEP16 represents the translocation pore for PORA (25). Originally OEP16 was isolated as a transmembrane-spanning protein of 16 kDa from the outer envelope membrane of pea chloroplasts (36). When reconstituted into lipid bilayer membranes, the corresponding recombinant Ps-OEP16 protein formed a slightly cation-selective channel with transport selectivity for amino acids and amines.…”
mentioning
confidence: 99%
“…HP20 itself or other PRAT proteins, such as HP22 or OEP16-1, 38 could serve as import channel. Alternatively, HP20 could insert into the outer envelope membrane spontaneously 39 or via an ankyrin-dependent mechanism 40,41 or could employ TOC75. 42 Work is in progress to explore these possibilities and further define the structure and function of the different PRAT proteins in mitochondria and chloroplasts.…”
Section: Summary and Perspectivesmentioning
confidence: 99%